Application of Wireless Network Based on Artificial Intelligence in Network Teaching of Preschool Education Manual and Aesthetic Education Practical Course. (15th June 2022) - Li, Xingping; Xiao, Wei
Abstract : For preschool education majors, art and crafts are required courses. This course is a hands-on exercise that helps students develop their creative awareness, design thinking, and hands-on skills. At the same time, it provides learners with the teaching thinking mode of art and handicraft theme and the form of online teaching helps learners to construct the thinking mode of online learning. As a new teaching form, online teaching is gradually leading the reform in the field of education. However, the majority of present online teaching is simply a continuation of traditional teaching thought, relying on substantial teaching research rather than utilizing its particular advantages to develop and expand. Also, the connotation depth of traditional teaching may not involve the essential problem of teaching application itself—teaching methods and experience of acquiring knowledge. As a result, determining how to characterize an individual's ability to acquire knowledge and successfully assessing the level of growth of an individual's cognitive structure is critical to the development of a new generation of online education. In order to prepare for the next generation of network teaching, this article uses artificial intelligence and wireless networks to teach preschool education manual and aesthetic education practical courses through the Internet. From the perspectives of individuals and groups, two teaching case recommendation experiments are given. The experiment's end result confirms the practicality and logic of the evaluation model described in this research, which is based on individual cognitive structure.